FORMULASI COOKIES SUMBER PROTEIN BERBAHAN TEPUNG KACANG TUNGGAK SEBAGAI UPAYA PEMANFAATAN KOMODITAS LOKAL - Erni Sofia Murtini; Nur Oktavia Suci Lestari (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Innovation of protein source cookies using local raw material such as cowpea is important for diversification. The objective of the study was to formulate cowpea cookies that meet the protein source claim based on Codex Alimentarius Commissary (CAC) and BPOM regulations. Formulation was determined by linear programming with minimum protein limits of 5 g/100 g for CAC and 12 g/100 g for BPOM. There were 6 formula with one factor, i.e. the proportion of the germinated cowpea flour:wheat flour of 44.58:4.42, 46.58:2.42, 48.58:0.42, 7.60:41.40, 9.60:39.40, and 11.60:37.40. The study was arranged in Randomized Block Design (RBD) and repeated 4 times. The data were analyzed by ANOVA followed by DMRT with 95% confidence level. The best formulation was obtained in cookies made with the proportion of germinated cowpea flour:wheat flour of 48.58 g:0.42 g. Those cookies contained 12.55±0.15% protein, 3.79±0.14% water, 36.18±1.42% fat, 45.09% carbohydrate, had yellow color (L* 61.62±0.42; a* 5.64±0.09; b* 23.52±0.36), 1.35±0.03 N break strength, 583 Kcal calories and 0.25±0.01% sodium. One serving size of the cookies (25 g) was able to meet the %daily value for protein (5.23%), carbohydrate (3.5%), fat (13.5%), and energy (6.5%). The cookies can be qualified as protein source products based on BPOM RI regulation (minimal 12 g/100 g protein) and Codex Alimentarius regulation (minimal 5 g/100 g protein), and complied with SNI quality standard for cookies that require maximum 5% water content and at least 5% protein.